Vie conjugale et abus de substances: interrelations et traitement - Tremblay, Joël; Bouchard, Geneviève; Bertrand, Karine (Canadian Journal of Counselling and Psychotherapy, 2009)
Although research confirms that it is beneficial to include the partner of the substance-addicted individual in the treatment of this addiction, couple therapy is rarely used in substance abuse treatment programs. The current article is aimed at improving knowledge transfer to counsellors on the relationships between substance abuse and conjugal life and on the usefulness of couple therapy in the treatment of alcoholism and drug abuse. The potential barriers encountered when moving an empirically supported treatment to “real world” settings are discussed and answers are proposed.